Development of Integrated Capacitance-Resistive Model Method to Estimate Multilayer Reservoir Performance - Tsabita Fadjar, Naura
Reservoir performance is vital to be predicted as a consideration in field development and optimization plan, furthermore, for a field which has a waterflooding program. Integrated Capacitance Resistive Model (ICRM) quickly and accurately could evaluate the performance of the waterflood field. So far, ICRM has been implemented by many for waterflooding simulation but only for a reservoir with a single layer. In this study describes the development of the ICRM equation and also the fractional oil flow model that is easy and proper to be applied in multilayer reservoir. The procedure of this ICRM application is with linear multivariate regression on production rate and cumulative water injection. A simple analytical approach is made to quantify the connectivity between layers, connectivity between wells, time response delay, and oil fractional flow so that specific solution for ICRM equation and fractional oil model is obtained for multilayer reservoir. Before parameters in each layer are quantified, connectivity between wells is established by fitting ICRM on cumulative liquid production data with the assumption that the reservoir is a single layer. After that, the value of those parameters for each layer is obtained using a straightforward approach. Lastly, the oil production model is built by fitting oil production rate data. ICRM equation and oil production model for multilayer reservoir are validated with synthetic field data for two layers case and three layers case. The validation result shows a good agreement between the oil production rate calculated by ICRM and oil production rate from synthetic field data. The development of this method is convincing to capture the reservoir behavior in layer scale.